DERMANYSSUS GALLINAE IN LAYING HENS FARMS IN ALGERIA: INFESTATION PREVALENCE AND MOLECULAR DETECTION OF SALMONELLA - Mohamed Douifi; Nassim Ouchene; Karim Rahal; Ahcène akem (Agricultura, 2018)
Dermanyssus gallinae (Red mite) is the most important and common ectoparasite of laying hens and recognized as a vector of several pathogens. In order to estimate the infestation prevalence rate of Dermanyssus gallinae in layer housing and to evaluate its vectorial role in regard to salmonella. A study was carried out in 386 laying hen farms in four provinces located in north-eastern Algeria. A total of 32 pooled mite samples were examined for the presence of Salmonella enterica, Salmonella typhimurium and Salmonella enteritidis using PCR essay. Results showed that 14% of hen housing were infested by D. gallinae. Salmonella enterica DNA was detected in 8 samples (25%), including two Salmonella enteritidis (6.25%). These results indicate that D. gallinae can act as reservoir of Salmonella, allowing the propagation of this bacterium between successive bands and between different farms.